Multifunctional Fructose 1,6-Bisphosphate Aldolase as a Therapeutic Target - Pirovich, David B.; Da’dara, Akram A.; Skelly, Patrick J. (Frontiers in Molecular Biosciences, 2021)
Fructose 1,6-bisphosphate aldolase is a ubiquitous cytosolic enzyme that catalyzes the fourth step of glycolysis. Aldolases are classified into three groups: Class-I, Class-IA, and Class-II; all classes share similar structural features but low amino acid identity. Apart from their conserved role in carbohydrate metabolism, aldolases have been reported to perform numerous non-enzymatic functions. Here we review the myriad “moonlighting” functions of this classical enzyme, many of which are centered on its ability to bind to an array of partner proteins that impact cellular scaffolding, signaling, transcription, and motility. In addition to the cytosolic location, aldolase has been found the extracellular surface of several pathogenic bacteria, fungi, protozoans, and metazoans. In the extracellular space, the enzyme has been reported to perform virulence-enhancing moonlighting functions e.g., plasminogen binding, host cell adhesion, and immunomodulation. Aldolase’s importance has made it both a drug target and vaccine candidate. In this review, we note the several inhibitors that have been synthesized with high specificity for the aldolases of pathogens and cancer cells and have been shown to inhibit classical enzyme activity and moonlighting functions. We also review the many trials in which recombinant aldolases have been used as vaccine targets against a wide variety of pathogenic organisms including bacteria, fungi, and metazoan parasites. Most of such trials generated significant protection from challenge infection, correlated with antigen-specific cellular and humoral immune responses. We argue that refinement of aldolase antigen preparations and expansion of immunization trials should be encouraged to promote the advancement of promising, protective aldolase vaccines.